KONSEP SEHAT SAKIT : SEBUAH KAJIAN FILSAFAT DALAM HUBUNGANNYA DENGAN INDUSTRI KEBUGARAN - Vincent Phan; David Setiawan; Cleon Dai Kumuda Aulia; Andrian Louise Tandra (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The profession of a doctor with its scientific tools has unique characteristics. This specificity can be seen from the justification given by law, namely from the permissibility of carrying out medical actions on the human body in an effort to maintain and improve health status. Medical actions against the human body such as surgery, transplantation, removal of certain parts of human organs carried out by doctors are not classified as criminal acts. Conversely, if the action is not carried out by a doctor, it will be classified as a crime. The medical profession is positioned as a noble profession (afficium mobile) similar to the advocate profession. This profession has a noble mission to help people who are experiencing difficulties. The purpose of this study was to analyze the legal responsibility of doctors for alleged medical malpractice for surgical procedures based on Law Number 29 of 2004 concerning Medical Practice and procedures for resolving reports of alleged medical malpractice from an internal view of the medical profession. The term malpractice in the health service sector has recently begun to be widely discussed by the public from various parties as a result of the many complaints of cases that are suspected of being malpractice according to the designations and terms in society against the medical profession which is considered to have harmed patients in doctors treating a patient. As for this research, it uses a normative juridical method supported by an approach to events or phenomena that occur in society. The promulgation and enforcement of legal norms on the limits of medical malpractice are best contained in the Law on Medical Practice, which is now in effect in Law Number 29. 2004 concerning the Implementation of Medical Practice and how accountability should be carried out in accordance with positive law in force in Indonesia.